2009
DOI: 10.1080/19371910802569716
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Expenditure as a Determinant of Health Status in Lesotho

Abstract: In this article, we have examined the relationship between public expenditure on health care and health status in Lesotho using an econometric technique-the error correction model. Three indicators of health status were used: life expectancy at birth (years), infant mortality rate (per 1,000 live births), and under-5 mortality rate (per 1,000). The results of our analyses provided evidence that in addition to public expenditure on health, the availability of physicians, female literacy, and child immunization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 7 publications
5
49
2
3
Order By: Relevance
“…Public health expenditure has been found to be significantly associated with improved health status in Lesotho [23] and Central America and the Caribbean [24]. A 2005 study of mortality levels and trends in China in the 1980s and 1990s found that public expenditure on education and health was significantly associated with increased life expectancy at birth [25].…”
Section: Introductionmentioning
confidence: 99%
“…Public health expenditure has been found to be significantly associated with improved health status in Lesotho [23] and Central America and the Caribbean [24]. A 2005 study of mortality levels and trends in China in the 1980s and 1990s found that public expenditure on education and health was significantly associated with increased life expectancy at birth [25].…”
Section: Introductionmentioning
confidence: 99%
“…Public spending on health is a core factor in determining health outcomes [14], [15], especially for the poor [16], and, although not universally accepted as a powerful determinant of overall mortality, it might also influence, to some degree, the probability of death [17][19]. Therefore, the per capita government expenditure on health, expressed in international dollars and calculated using purchasing power parities (PPPs), was extracted from the World Health Information Statistical Information System (WHOSIS).…”
Section: Methodsmentioning
confidence: 99%
“…Ziesemer (2012) examines 65 low-income countries out of which 39 are SSA countries from 1960 to 2010, and finds that the growth rates of aid per capita have significantly favorable effects on the growth rates of life expectancy. In a study of Lesotho from 1980to 2001, Akinkugbe and Mohanoe (2009 use an error correction model (ECM) and find that in addition to public healthcare expenditure, the availability of physicians, female literacy, and child immunization positively and significantly influenced health outcomes. Gomanee, Morrissey, Mosley, and Verschoor (2005) study 104 countries of which 37 are SSA over the years 1980-2000, and find that aid can improve human welfare through increases in certain public expenditures, supporting the public interest predictions, and that this effect appears to be greater in low-income countries.…”
Section: Literature Reviewmentioning
confidence: 99%